Research Development on Sustainable Business Models - Loso Judijanto (Westscience Press, 2024)
This study presents a comprehensive bibliometric analysis of the research on sustainable business models, drawing from the Google Scholar database and focusing on the period from 1991 to 2024. The analysis identifies key themes, influential authors, and collaborative networks within the field, highlighting the central role of sustainable business practices, the increasing importance of digital transformation, and the adoption of circular economy principles. By mapping the intellectual structure of the field, the study provides valuable insights into the evolution of sustainable business models and suggests pathways for future research. The findings emphasize the need for interdisciplinary collaboration and the integration of innovative strategies to advance sustainability in business. Despite its limitations, this study offers practical implications for academics, businesses, and policymakers, aiming to align research and practice with global sustainability goals.